Study of serum level of cathelicidin in patients with inflammatory bowel disease and its correlation to disease activity - Abeer A Mohamed; Amani K Mohamed; Radwa S Shahin; Fatma M El-Senosy (Wolters Kluwer Medknow Publications, 2020)
Introduction Inflammatory bowel disease (IBD) includes ulcerative colitis (UC) and Crohn's disease (CD). Genetic susceptibility together with environmental factors disturbs intestinal homeostasis, resulting in repeated and chronic inflammation with remission and exacerbation cycles. Cathelicidin (LL-37) is an antimicrobial peptide known to be associated with various autoimmune diseases. The authors have attempted to determine if cathelicidin can accurately reflect IBD disease activity. The authors hypothesized that serum cathelicidin correlates with mucosal disease activity. Aims The aim was to correlate circulating cathelicidin level with mucosal disease activity in patient with IBD. Patients and methods This is a case-control study that was conducted on 90 adult participants, comprising 60 patients with IBD and 30 non-IBD cases studied as a control group, who attended the gastrointestinal endoscopy and liver unit at Al-Zahraa University and El-Haram Hospital. All participants were subjected to complete medical history, physical examination, laboratory investigations, and colonoscopic examination. LL-37 levels were determined by enzyme-linked immunosorbent assay. Data from patients were used for calculation of accuracies in indicating mucosal disease activity. Results There was a highly significant increase of serum LL-37 level in patients with IBD than control. Serum cathelicidin level was negatively correlated with partial Mayo scores for patients with UC and Harvey-Bradshaw indices for patients with CD. Among patients with IBD, low LL-37 level indicates moderate or severe disease activity, and high LL-37 level indicates remission. C-reactive protein (CRP) levels were directly correlated with partial Mayo score for patients with UC and Harvey-Bradshaw index for patients with CD. Co-evaluation of LL-37 and CRP levels was more accurate than CRP alone or LL-37 alone in the correlation with Mayo endoscopic score for patients with UC. Conclusion Patients with IBD have increased serum level of LL-37. Evaluation of both LL-37 and CRP can indicate mucosal disease activity in patients with UC, and both in combination are better indicators than LL-37 or CRP alone.